Congress volume : Paris, 1992 - Emerton, John Adney. (Supplements to Vetus Testamentum, 1995)
The twenty articles collected in this volume cover a wide range of subjects concerned with the Old Testament: religion (the divine name Shaddai; dominant religious ideas between 1500 and 600 B.C.; exclusiveness; the kingship of God), The Pentateuch (Genesis xviiii-xix; Og's iron bed; laws in Deuteronomy and Middle Assyrian laws; the Pentateuch, The Deuteronomist and Spinoza), the historical books, history and archaeology (Ugarit and Israelite origins; Arameans; the system of the twelve tribes of Israel; the text of the historical books; 1 Kings xiii; places for women in Israelite cities), the prophetical books (Amos and Hosea; Isaiah), The Apocrypha and Pseudepigrapha (Women in Ecclesiasticus and Judith; the origin of evil in apocalyptic and the Dead Sea Scrolls), and literary conventions (the explicit and the implicit; proleptic summaries). The articles (in English, French or German) were written by scholars with varying religious backgrounds from various countries, and were originally read at a Congress in Paris of the International Organization for the Study of the Old Testament in 1992.